Level Of Knowledge Regarding Rch Services Among Subcentre Health Functionaries Of Kalyanpur Block, Kanpur - Kaushal, S K; Saxena, S C; Srivastava, V K; Nigam, Seema; Srivastava, J P (Indian Journal of Community Health, 2006)
Objectives : 1) To assess the level of knowledge among sub centre level health functionaries. 2) To identify weaker areas of RCH related knowledge 3) To suggest areas of relevant knowledge improvement. Setting : Sub Centre Study Design: Cross Sectional Participant : BHW-F (ANM), BHW-M (Multi Purpose worker Male) Study Period : Jun to Dec'2004 Study Variable : RCH Programme, Antenatal, Natal, Post Natal Services, Immunization, Contraceptive. Statistical Analysis : Percentage Result : Knowledge regarding new component like adolescent health, RTI/STD/HIV/AIDS was found poor. Level of knowledge regarding management of ARI.Vit A supplementation, Post natal care, New born care, emergency contraceptive was found to be unsatisfactory.